Assemblage reorganization of South African dragonflies due to climate change. Issue 12 (5th October 2021) - Basel, Ashleigh M.; Simaika, John P.; Samways, Michael J.; Midgley, Guy F.; MacFadyen, Sandra; Hui, Cang
Abstract: Aim: Climate change is expected to cause large shifts in species assemblages such as dragonflies and damselflies (Insecta: Odonata). Here, we assess the influence of environmental drivers of turnover on Odonata assemblages. Secondly, we map the predicted spatial variation in species composition, first as a gradient of assemblage similarity, and then as discrete bioregions delineating major areas of odonate endemism. Finally, we map the magnitude of expected change in species turnover in response to climate change under two emission scenarios. Location: South Africa. Methods: We used a spatial database comprising of 164 species of odonates and 20 covariates, to explore changes in compositional turnover using generalized dissimilarity models. Bioregions were compiled through various clustering techniques. Results: Present‐day odonate bioregions correspond to climatic zones and are clearly separated by transitional zones with rapid spatial turnover. Present odonate bioregions are projected to undergo extensive reorganization by 2050 and 2070. Temporal turnover in species composition is expected to reach up to 80% in the large arid interior and 64% along the coast. Half of all South Africa's protected areas are likely to experience climate induced changes to dragonfly bioregions in the near future. Main conclusions: Species assemblages are rapidly changing. This work highlights future shifts in climate will result in complex and nonlinear responses in Odonata communities. With ongoing climate change, current odonate bioregions are predicted to expand while others will contract considerably in size within the next 30 years. The current demarcated protected areas may be inadequate to protect dragonflies as climates change. Odonata can be used to track forefronts of climate change, which will likely affect a larger array of taxa as well.